Thermal and mechanical properties of poly(arylene ether ketone)s based on 5-tert-butyl-1,3-bis(4-fluorobenzoyl)benzene - (:unkn) unknown (WILEY-V C H VERLAG GMBH, 2001)
An aromatic bishalide, 5-tert-butyl-1,3-bis(4-fluorobenzoyl)benzene (2) was synthesized in high yield and purity by the reaction of 5-tert-butylisophthaloyl chloride. (1) and flurorbenzene and polymerized by nucleophilic substitution reaction with commercially available aromatic bisphenols to prepare a series of high molecular weight poly(arylene ether ketone)s containing pendant tertiary butyl groups. The effect of molecular structure on the physical, thermal, mechanical and adhesion properties of the polymers was investigated.
Keywords: BIS(ARYL CHLORIDE)S; COMPOSITES